Valida????o do protocolo term??metro de seguran??a na maternidade de um hospital universit??rio no munic??pio de S??o Paulo/SP - Horvath, Elizienne de Sousa Costa (2018)
Introduction: The use of protocols such as the standard operating procedure assists in the sequencing and standardization of the pipeline to be taken, which facilitates the decisions of health professionals. In Brazil there is a shortage of data in the obstetrics and neonatal context, there is a lack of instruments and standardization of protocols for this purpose. Method: descriptive, qualitative study of technology validation of type development research. Objective: To evaluate a protocol in the model of standard operating procedure for implementation of the instrument defined as Safety Thermometer in Maternity in a public university hospital. Results: The results were obtained in two stages, the first consisted in the process of elaboration of the protocol by the researchers and validation by the committee of 12 specialists in obstetric nursing, professionals of the study unit, the analysis was done through the Content Validation Index (value of reference IVC = 0.80) using a semi-structured questionnaire with a Likert scale (1 to 4), the IVC scores of the specialists ranged from 0.84% to 1.0 and the concordance percentage was 98.7%. The second stage of the study consisted of the application of the instrument Maternity Safety Thermometer. The data obtained in this stage showed that the majority of the women was submitted to caesarean section 20 (64.5%). Of those who had vaginal deliveries, there was perineal trauma in 4 (12.8%) and 1 (3.2%) episiotomy; 3 (9.6%) had hemorrhage, the transfusion rate was 3.2% and that of infections 4 (12.8%). Of the newborns, 14 (45.2%) of the babies had to be transferred, 11 (35.5%) of which were foreseen. From the perception of the woman, 39.1% reported being separated from the baby and 7.4% were left alone, 38.4% considered that they were not taken seriously when showing concern. The indicator free of damage was 9.6%. Conclusion: The Maternity Safety Thermometer Protocol in the standard operating procedure format presented acceptable psychometric indicators of acceptable content validity, corroborating the use of the instrument considered easy to apply and enabling the production of safety indicators for obstetric and neonatal care.